2018
DOI: 10.1021/acsnano.8b02647
|View full text |Cite
|
Sign up to set email alerts
|

Proximity-Induced Magnetic Order in a Transferred Topological Insulator Thin Film on a Magnetic Insulator

Abstract: Breaking the time reversal symmetry (TRS) in a topological insulator (TI) by introducing a magnetic order gives rise to exotic quantum phenomena. One of the promising routes to inducing a magnetic order in a TI is utilizing magnetic proximity effect between a TI and a strong magnetic insulator (MI). In this article, we demonstrate a TI/MI heterostructure prepared through transferring a molecular beam epitaxy (MBE)-grown BiSe film onto a yttrium iron garnet (YIG) substrate via wet transfer. The transferred BiSe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 59 publications
4
50
0
1
Order By: Relevance
“…In order to probe the AHE signal, we performed the Hall measurement on two BST (6 QL)/CGT samples with different carrier types (one p-and the other n-type, denoted as Sample P and Sample N respectively), as shown in Figure 3 for Sample P and 145 Ω for Sample N, more than one order larger than the RAH values reported in previous works. [16][17][18]21 Absence of hysteresis in RAH is due to softness of the ferromagnetism and is consistent with the magnetization data ( Figure 1(d)) of the CGT substrate. 24…”
supporting
confidence: 80%
See 1 more Smart Citation
“…In order to probe the AHE signal, we performed the Hall measurement on two BST (6 QL)/CGT samples with different carrier types (one p-and the other n-type, denoted as Sample P and Sample N respectively), as shown in Figure 3 for Sample P and 145 Ω for Sample N, more than one order larger than the RAH values reported in previous works. [16][17][18]21 Absence of hysteresis in RAH is due to softness of the ferromagnetism and is consistent with the magnetization data ( Figure 1(d)) of the CGT substrate. 24…”
supporting
confidence: 80%
“…It is also notable that a recent work reported that CGT flake imprints its magnetization in the AHE of Pt thin film deposited on top, 32 Figure 4. [16][17][18]21 From Figure 4, we can see that the BST/CGT system is significantly better than previous proximity systems, based on both and tan values. The and tan achieved in Sample P (N) are 153 Ω (145 Ω) and 0.01286 (0.00715), respectively, more than one order larger than previous proximity-coupled systems.…”
mentioning
confidence: 99%
“…Experimentally, high-quality Cr 2 O 3 can be readily grown on the Al 2 O 3 (0001) via either sputtering, pulsed laser deposition, or molecular beam epitaxy (MBE), as the two materials have similar lattice constants and the same crystal symmetry. [12][13][14] Given our previous experience of the Cr:(Bi,Sb) 2 Te 3 growth on the Al 2 O 3 (0001) substrate, [15] the realization of a QAH insulator on Cr 2 O 3 is thus feasible. Furthermore, Cr 2 O 3 is a magnetoelectric material in which a net magnetic moment can be induced by applying an electric field.…”
Section: Integration Of a Quantum Anomalous Hall Insulator With A Magmentioning
confidence: 99%
“…A small exchange gap is opened in the TSS because of the magnetic dopant that breaks time‐reversal symmetry in the Cr‐BST layer. [ 27,28 ] If the Fermi circle of the TSS in the k ‐space is shifted by a DC current along the x ‐axis, the spin‐momentum locking will lead to a spin accumulation transverse to the x ‐direction. The bilayer film was then fabricated into devices with Hall bar geometry by photolithography for magneto‐transport and optical measurements (Figure 1c).…”
Section: Figurementioning
confidence: 99%